On the formation of hydrogen peroxide in water microdroplets. Issue 9 (9th February 2022) - Gallo Jr., Adair; Musskopf, Nayara H.; Liu, Xinlei; Yang, Ziqiang; Petry, Jeferson; Zhang, Peng; Thoroddsen, Sigurdur; Im, Hong; Mishra, Himanshu
Abstract : A. Gallo Jr, H. Mishra et al., pinpoint the origins of the spontaneous H2 O2 formation in water microdroplets formed via spraying or condensation, i.e., without the addition of electrical energy, catalyst, or co-solvent. Abstract : Recent reports on the formation of hydrogen peroxide (H2 O2 ) in water microdroplets produced via pneumatic spraying or capillary condensation have garnered significant attention. How covalent bonds in water could break under such mild conditions challenges our textbook understanding of physical chemistry and water. While there is no definitive answer, it has been speculated that ultrahigh electric fields at the air–water interface are responsible for this chemical transformation. Here, we report on our comprehensive experimental investigation of H2 O2 formation in (i) water microdroplets sprayed over a range of liquid flow-rates, (shearing) air flow rates, and air composition, and (ii) water microdroplets condensed on hydrophobic substrates formed via hot water or humidifier under controlled air composition. Specifically, we assessed the contributions of the evaporative concentration and shock waves in sprays and the effects of trace O3 (g) on the H2 O2 formation. Glovebox experiments revealed that the H2 O2 formation in water microdroplets was most sensitive to the air–borne ozone (O3 ) concentration. In the absence of O3 (g), we could not detect H2 O2 (aq) in sprays or condensates (detection limit ≥250 nM). In contrast, microdroplets exposed to atmospherically relevant O3 (g) concentration (10–100 ppb) formed 2–30 µM H2 O2 (aq), increasing with the gas–liquid surface area, mixing, and contact duration. Thus, the water surface area facilitates the O3 (g) mass transfer, which is followed by the chemical transformation of O3 (aq) into H2 O2 (aq). These findings should also help us understand the implications of this chemistry in natural and applied contexts.